Aplikasi Kegiatan Desa Berbasis Web dan MySQL di Desa Tenjojaya Kec. Cicurug Kab. Sukabumi - Dedi Kustiawan (BUANA INFORMATIKA CBI, 2019)
This study aims to develop information systems activities in the village of Tenjolaya with Web-based, and this study also aims to facilitate the Head of general affairs and Administration to record and record the activities of Tenjolaya Village. Recording and data collection activities in the village of Tenjolaya still using the manual way of recording and recording all village activities with handwritten which of course not yet programmed and can not be accessed freely anywhere and anytime. If the recording and data collection is still manual, will cause difficulties when looking for data when the data is needed. Therefore the need for a program or application that can facilitate in informing the activities of Desa Tenjolaya effectively and efficiently. To solve this problem, it takes an application using PHP and MySQL database, which this application can facilitate the Head of General Affairs and Administration in completing its tasks, especially in recording and data collection of village activities. With this application, is expected to upgrade the existing system into a computerized system that is more structured and programmed, so that recording and data collection of village activities will be faster,accurate and more quality information produced. Besides, with this application,Head of General Affairs and Administration can easily and neatly in accessing data of village activities.